Long-Lasting Effects of Communist Indoctrination in School: Evidence from Poland - Joan Costa-i-Font; Jorge García-Hombrados; Anna Nicińska (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Education can serve skill formation and socialisation goals both of which are conducive to desirable economic outcomes. However, the political manipulation of the school curricula can give rise to indoctrination effects with counterproductive welfare consequences on its pupils. This paper studies the effects of communist indoctrination on human capital accumulation and labour market outcomes in Poland. We document that the reduction of Marxist-Leninist indoctrination in school curriculum after 1954 exerted long-lasting beneficial effects. Unlike in East Germany, the school reform after the fall of communism in Poland had negligible effects on human capital and labour market outcomes. Our results are in contrast, explained by the ideological content of the school curriculum in the Polish education system.
Keywords: I28; 330; education systems; communist education; education reforms; school curriculum; later life outcomes; human capital attainment; labour market participation